VARIABLE ORDER VARIABLE STEPSIZE ALGORITHM FOR THE NUMERICAL SOLUTION OF DELAY DIFFERENTIAL EQUATIONS IN DIVIDED DIFFERENCE FORM - Fuziyah bt Ishak (Proceedings of ICMSA, 2006)
A variable order variable stepsize algorithm for the numerical solution of delay differential equations is described. The algorithm is adapted from the algorithms developed by Suleiman [10] and Omar [8] for the numerical solution of ordinary differential equations. The algorithm is based on the variable step formulation of the Adams method in divided difference form. The predictor-corrector mode using Adams-Bashforth and Adams-Moulton formulae are implemented. This algorithm proves to be reliable, accurate and efficient. The results of four test examples are presented.